APLIKASI PENCARIAN LOKASI WISATA KULINER BERBASIS ANDROID - , HANA ANDIANA MAULIDA; , Faizah, S.Kom., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Culinary offered from every city in Indonesia is growing and varied. Ranging from typical regional foods that are traditional to fast food. It also occurs in the development of smartphones. Nowadays, mobile phone which is commonly known as smart phone is not only used as a tool for sending message or communication, but also it is used for finding location, sharing pictures, even social media have been equipped with modern features, such as Google Maps. One of the widely used operating system on a smartphone is android. Based on the description above, it developed a culinary tourist location search application based on Android. This application is developed by using Java programming language, using MySQL basis data, and using feature of Google maps and GPS which are owned by android operation system. According to the result of the testing, this application can be used as a tool for searching the culinary location with keyword, searching the culinary location which is nearest to the user, searching kinds of category of culinary, it can give the information about rate by the users, saving the data of the user itself, it can save the new culinary location, give the complete information of each culinary location, give the direction of the culinary location, can make a call for the culinary place, and save rating from users on the culinary location.